NEUROGENIC DISFUNCTIONS OF LOWER URINARY TRACT (NDLUT) - Y. G. Alyaev; Z. K. Gadzhieva; Y. B. Kazilov (Сеченовский вестник)
The characteristic features of neurogenic disfunctions of lower urinary tract are analized in this article.